Chemical composition and herbicidal action of essential oil from Tagetes erecta L. leaves - Laosinwattana, Chamroon; Wichittrakarn, Pattharin; Teerarak, Montinee (My University, 2018)
Plant derived substances, particularly essential oils have been an increasing interest in their safe and environmentally-friendly application to crops, as a powerful alternative to chemical herbicides. The present investigation studied the chemical composition of the essential oil extracted from Tagetes erecta L. and evaluated its herbicidal activities (pre-and post-emergence) against Echinochloa cruss-galli (L.) Beauv. The yield of essential oil from T. erecta was 0.72 mg.kg−1 fresh weight. Gas chromatography-mass spectrometry was employed to determine essential oil chemical composition. Relatively high amounts of monoterpines were detected, consisting mainly of piperitone (17.12%), piperitenone (10.46), and ocimine (8.59%); identified sesquiterpenoids consisted mainly of neophytadiene (16.18%) and caryophyllene (11.10%). The essential oil was formulated as emulsifiable concentrate (EC-EO) for herbicidal applications. Seed germination and seedling growth of E. crus-galli was determined by Petri dish bioassay for EC-EO concentrations ranging from 0.25 to 2 mL.L−1. At 2 mL.L−1, the EC-EO completely inhibited germination and growth of E. crus-galli seed due to the inhibition of α-amylase activity. Post-emergence application of EC-EOs was also tested, with concentrations of 10 to 80 mL.L−1 foliar applied to 21-day-old E. crus-galli plants. The leaves of treated plants appeared wilted and desiccated. Increasing concentrations of oil decreased chlorophyll a, b, and carotenoid content, indicating that the EC-EO interferes with photosynthetic metabolism. The EC-EOs also caused loss of membrane integrity and increase of thiobarbituric acid reactive substances. Taken together, these results indicate that the T. erecta essential oil has phytotoxic compounds that could be utilized as natural herbicides for future weed control.
Keywords: Allelopathic; Essential oil; Post-emergence; Pre-emergence; Tagetes erecta